(untitled) (Archaeologia Adriatica, 2012)
In the course of 2006, the Archaeology Department of Varaždin Town Museum conducted the first major archaeological excavations of the outer fortification structures of the Old Town (Stari Grad). During the excavation of the northern and western wet ditches, dug in the course of the 16th century at the time of the large Renaissance modernisation of the mediaeval fort, numerous and various archaeological artefacts were collected. The artefacts were damaged and unusable, and had been thrown into the water of the defence ditch as useless rubbish. Simple conical glasses were identified among the large quantity of various pieces of ceramic crockery. These form one of the categories of tableware: drinking vessels. In an analysis of finds unearthed in this campaign, thirteen glasses of the same type have been identified. Although they differ in certain details, they still represent a recognisable typological category and are classified as simple conical glasses. Their stratigraphic location, as well as a comparison with known specimens from other sites dates the glasses to the Late Middle Ages and the 15th century, with their possible use also at the beginning of the 16th century. Given their simple workmanship, modest decoration and mass production, they indicate local production, and their use is associated with members of lower social classes inside the feudal fortifications.